2015
DOI: 10.1039/c4cp05425c
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond surface dynamics in genomic DNA from in vitro-grown plant species: a SERS assessment

Abstract: In this work the surface-enhanced Raman total half band widths of seven genomic DNAs from leaves of chrysanthemum (Dendranthema grandiflora Ramat.), common sundew (Drosera rotundifolia L.), edelweiss (Leontopodium alpinum Cass), Epilobium hirsutum L., Hypericum richeri ssp. transsilvanicum (Čelak) Ciocârlan, rose (Rosa x hybrida L.) and redwood (Sequoia sempervirens D. Don. Endl.) have been measured. We have shown that surface-enhanced Raman spectroscopy (SERS) can be used to study the fast subpicosecond dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…The observed differences in the SERS results of Muntean et al and the present study are possibly due to the changes in the adsorption pattern of the nucleotide bases on the metal NPs surfaces. In addition, the excitation wavelengths of 514, 633, and 785 nm with the laser powers of 10, 17, and 100 mW were used in the present study, whereas the SERS measurements by Muntean et al were carried out using the frequency‐doubled output of pulsed Nd 3+ :YAG laser emitting at 532 nm with laser power of 45 mW. The use of pulsed laser may lead to higher peak power and local heating of DNA samples.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…The observed differences in the SERS results of Muntean et al and the present study are possibly due to the changes in the adsorption pattern of the nucleotide bases on the metal NPs surfaces. In addition, the excitation wavelengths of 514, 633, and 785 nm with the laser powers of 10, 17, and 100 mW were used in the present study, whereas the SERS measurements by Muntean et al were carried out using the frequency‐doubled output of pulsed Nd 3+ :YAG laser emitting at 532 nm with laser power of 45 mW. The use of pulsed laser may lead to higher peak power and local heating of DNA samples.…”
Section: Resultscontrasting
confidence: 83%
“…The SERS results of gDNA from B. juncea plant observed in the present study were compared with the previous results on SERS of plant DNA, which illustrated that in contrast to the study of Muntean et al where intense peaks were observed around 1600, 1360, and 1300 cm −1 , our results and those of Qiu et al as well as Liu et al found weak peaks in the region 1150–1800 cm −1 and strong peaks at 625, 718, and 1013 cm −1 . The observed differences in the SERS results of Muntean et al and the present study are possibly due to the changes in the adsorption pattern of the nucleotide bases on the metal NPs surfaces. In addition, the excitation wavelengths of 514, 633, and 785 nm with the laser powers of 10, 17, and 100 mW were used in the present study, whereas the SERS measurements by Muntean et al were carried out using the frequency‐doubled output of pulsed Nd 3+ :YAG laser emitting at 532 nm with laser power of 45 mW.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The study of vibrational spectra of the nucleotides in the dynamic interaction with the metallic nanoparticles (NP) [44,45] located close to graphene nanopore can combine translocation localization and nucleotide interaction enhancement or modification due to (1) the graphene LJ interaction and (2) the Au LJ interaction. For the initial interaction of the Au20 nanoparticle with cytosine nucleotide, the Au20 NP was localized close to the cytosine initial position as it is shown in…”
Section: Model and Methodsmentioning
confidence: 99%
“…Previously, monitoring the changes in the normal Raman full widths at half-maximum (fwhm’s) and, correspondingly, in the global relaxation times of the functional groups in DNA, upon varying the physicochemical parameters, was of interest. , In these cases, solution dynamics of nucleic acids was under study. Besides, the surface dynamics of plant genomic DNA on silver nanoparticles was reported by us for several cases using surface-enhanced Raman scattering (SERS) (refs and and references therein).…”
Section: Introductionmentioning
confidence: 94%